2013
DOI: 10.1186/1752-153x-7-116
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl and butyryl cholinesterase inhibitory sesquiterpene lactones from Amberboa ramosa

Abstract: BackgroundAlzheimer’s disease (AD) is characterized by a progressive memory loss that leads to a profound emotional disturbance in later stages. As no safe and effective drug is yet available for the treatment of AD, secondary metabolites from plants may be instrumental in meeting this challenge. Keeping in view this point we evaluated sesquiterpenes of medicinal plant Amberboa ramosa for their cholinesterase inhibitory activity.ResultsFour sesquiterpene lactones have been isolated from the ethyl acetate solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…From ancient times, man has always used herbs for various liver disorders as a treatment strategy, because natural remedies from traditional medicinal plants have proven to be effective alternative treatments in cases of liver injury. From various studies, it has been found that hepatoprotective effects are directly associated with phytoconstituents (Sabir and Rocha, 2008;Choi et al, 2009;Bhaskar and Balakrishnan, 2010;Huang et al, 2010;Nayak et al, 2011;Rehman et al, 2012;Ibrahim et al, 2013). All around the world, and especially in developing countries, people use traditional herbal medicines; therefore, there is a strong need to develop such a hepatoprotective medicine using natural products that can pass the safety evaluation and screening in the early phase of drug discovery because most toxic compounds are metabolized in the liver (Iwalokun et al, 2006;Adeneye, 2009;Ajiboye et al, 2010;Ahmed et al, 2013;Chanda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From ancient times, man has always used herbs for various liver disorders as a treatment strategy, because natural remedies from traditional medicinal plants have proven to be effective alternative treatments in cases of liver injury. From various studies, it has been found that hepatoprotective effects are directly associated with phytoconstituents (Sabir and Rocha, 2008;Choi et al, 2009;Bhaskar and Balakrishnan, 2010;Huang et al, 2010;Nayak et al, 2011;Rehman et al, 2012;Ibrahim et al, 2013). All around the world, and especially in developing countries, people use traditional herbal medicines; therefore, there is a strong need to develop such a hepatoprotective medicine using natural products that can pass the safety evaluation and screening in the early phase of drug discovery because most toxic compounds are metabolized in the liver (Iwalokun et al, 2006;Adeneye, 2009;Ajiboye et al, 2010;Ahmed et al, 2013;Chanda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of herbal formulations have been affirmed to have medicinal properties to cure several life-threatening diseases (Sabir and Rocha, 2008;Akash et al, 2011;Akash et al, 2014a,b;Bhaskar and Balakrishnan, 2010;Huang et al, 2010;Venkatesh et al, 2010;Nayak et al, 2011;Rehman et al, 2012;Ibrahim et al, 2013;Hussain et al, 2014;Parveen et al, 2014). The plants that exhibit hepatoprotective effects, have the phytoconstituents such as phenyl compounds, coumarins, essential oils, monoterpenoids, diterpenoids, triterpenoids, steroids, alkaloids and other nitrogenous compounds (Sharma et al, 2011;Valan et al, 2010) that reveal hepatoprotective effects by preventing the liver from the damaging effects of drug-induced intoxication .…”
Section: Discussionmentioning
confidence: 99%
“…There are not as many reports about AChEI activity of sesquiterpenes as alkaloids, but the existing data are indicative of the mentioned activity in some herbs and their sesquiterpene constituents. The results of isolating sesquiterpene lactones from Amberboa ramosa, a plant of Asteraceae, have revealed their excellent AChEI activity (Ibrahim et al 2013); while the leaves essential oil of Hedychium gardnerianum has exhibited AChEI activity (Arruda et al 2012) recommending the oil to be used in aromatherapy. Since the constituents were mostly found to be sesquiterpenes, the authors had concluded that the AChEI activity was due to the presence of these compounds.…”
Section: Introductionmentioning
confidence: 99%